Reactive spark plasma sintering of NiAl intermetallics: A comparative study. (January 2023) - Abedi, Mohammad; Kuskov, Kirill; Moskovskikh, Dmitry; Zakharova, Elena V.; Belov, Dmitry; Mukasyan, Alexander
Abstract: Reactive spark plasma sintering (RSPS) is an effective method for the consolidation of refractory compounds, including intermetallics. RSPS involves the SPS consolidation process and chemical reactions. SPS parameters such as the heating rate, maximum temperature, and dwell time influence the kinetics of the chemical reaction. To control the sintering process, it is critical to understand the relationship between the SPS parameters and different reaction modes. For a highly reactive Ni–Al system, we directly compare the consolidation kinetics under various SPS conditions. Comparing the RSPS and SPS schemes, we unequivocally conclude that the reactive mode permits an overall higher densification for the considered system. Two RSPS strategies are identified: i) RSPS under self-sustained reaction conditions occurring under a high heating rate and large volume-to-surface ratio, and ii) RSPS under relatively slow reaction rate conditions. The question of which strategy is best is addressed based on an analysis of the microstructures and mechanical properties of the fabricated materials. Highlights: Direct comparison of SPS, RSPS and RFSPS consolidate mode for intermetallic system. Unequivocally showed that the reactive modes permit a higher densification. The optimum consolidation strategies are suggested. Material with exceptionally high mechanical properties fabricated in a minute.